Development of gluten‑free and egg‑free pasta based on quinoa (Chenopdium quinoa Willd) with addition of lupine four, vegetable proteins and the oxidizing enzyme POx - Linares-García, Laura (2019)
Universidad Nacional Agraria La Molina. Facultad de Industrias Alimentarias